(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
The study investigated Influence of educational management support services on students retention in public universities in Rivers State. Two research questions and two hypotheses were formulated. The study adopted a descriptive survey design. The population stood at 12,543 which comprised 3,762 lecturers and 8,780 students across public universities in Rivers State. The sample size which stood at 745 respondents, was determined using Taro Yamen formula. Stratified sampling technique was use in selecting the respondents, comprising 362 lecturers and 383 students in public universities in Rivers State. The instruments for data collection were two self-structured questionnaires titled: “Influence of Educational Management Support Services Questionnaire (IEMSSQ) and Students Retention in Public Universities Questionnaire (SRPUQ)”.The instrument was validated by two experts in the field of Measurement and Evaluation in Rivers State University. Cronbach Alpha method was used to establish the overall reliability index of 0.81. Mean and standard deviation were used to answer the research questions, while z-test statistics was used to test the null hypotheses at 0.05 alpha level of significance. The findings of the study revealed that, academic advising services, Counselling and Psychological Services influence students’ retention in Public Universities in Rivers State to a high extent. Based on the findings of the study, the researcher recommends among others that, Heads of Departments and Deans of faculties in the various Universities should make academic advising, counselling and Psychological Services core components of student support services.